(untitled) (Geologica Macedonica, 2023)
This paper presents the results of the investigations of volcanic rocks of Middle Miocene age in the central parts of the Varadar zone for the first time. The volcanic rocks that appear in the Čitakliјa locality, according to their petrological and mineralogical characteristics, represent basic igneous rocks and they are transitional rocks between phonotephrites and high potassium shoshonites. The geochemical distribution of trace elements and elements from the group of rare earths (REE), as well as isotopes of 87Sr/86Sr (0.708348) and isotope values of 143Nd/144Nd (0.512319) indicate the fact that the magmatic sources of these rocks can be located in the border region between the upper mantle and the lower part of the continental crust.